IMPROVEMENT OF DIAGNOSIS METHODS FOR DESTRUCTIVE FORMS OF ACUTE CALCULOSIS CHOLECYSTITIS. - Khaydarov Farrukh Nuritdinovich. (Scholar Express Journals, 2022)
The diagnostic significance of procalcitonin and lactoferrin in destructive forms of acute calculouscholecystitis has been studied. 91 patients with acute calculouscholecystitis were examined, who were divided into 2 age groups; group I (48) patients under 65 years of age, group 2 (43) patients over 65 years of age. The content of lactoferrin and procalcitonin in blood serum was studied by the method of enzyme immunoassay in ng/ml by commercial test systems of Vector-Best CJSC. A comparative analysis of the dynamic study showed a clear dependence of the concentration of procalcitonin and lactoferrin in the blood with the degree of destructive process in the gallbladder wall, which was more pronounced in patients older than 65 years. The high informative value of studies of the content of procalcitonin and lactoferrin in the blood serum of patients for the diagnosis of destructive forms of acute calculouscholecystitis has been proved.
Keywords: Destructive cholecystitis; lactoferrin; procalcitonin